2016
DOI: 10.1111/asj.12606
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high‐fat diet promotes onset of diabetes in rat offspring

Abstract: The onset and progression of type II diabetes is closely related to environmental factors, in particular dietary habit. Moreover, the environmental exposures very early in life can influence the risk for development of type II diabetes later in life. In this study, we investigated pathophysiological changes in the pups of maternal Spontaneously Diabetic Torii (SDT) rats that were fed a high-fat diet (HFD) throughout gestation and lactation. Maternal SDT rats were continued on HFD for 5 weeks, from day 8 of ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, the etiology and pathogenesis of obesity and diabetes are still unclear. Since the developmental origins of health and disease (DOHaD) hypothesis was first put forward in the early 1990s ( 1 ), a large number of epidemiological investigations ( 2 4 ) and animal studies ( 5 , 6 ) have highlighted the importance of the developmental environment in early life in determining the trajectories of chronic disease in later life, including obesity and T2DM. Numerous recent studies ( 7 , 8 ) and our previous research ( 9 ) have shown that a maternal high-fat diet during pregnancy and lactation can significantly increase the susceptibility of offspring to obesity, glucose intolerance and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the etiology and pathogenesis of obesity and diabetes are still unclear. Since the developmental origins of health and disease (DOHaD) hypothesis was first put forward in the early 1990s ( 1 ), a large number of epidemiological investigations ( 2 4 ) and animal studies ( 5 , 6 ) have highlighted the importance of the developmental environment in early life in determining the trajectories of chronic disease in later life, including obesity and T2DM. Numerous recent studies ( 7 , 8 ) and our previous research ( 9 ) have shown that a maternal high-fat diet during pregnancy and lactation can significantly increase the susceptibility of offspring to obesity, glucose intolerance and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that obesity and maternal overnutrition create changes in uterine milieu during pregnancy leading to developmental alterations and defects in organ function and metabolism in offspring [ 3 , 4 ]. Also, maternal nutritional programming by hypercaloric diets exposure that simulate Western diets, such as high fat diet (HFD), cafeteria diet (CAF) or high sugar diet (HSD) in murine models, change offspring metabolism leading to insulin resistance, type 2 diabetes mellitus (T2DM) [ 5 7 ], cardiovascular diseases and hypertension [ 8 ], non-alcoholic liver diseases and steatohepatitis [ 9 , 10 ]. Defective molecular pathways related to maternal programming by nutrient oversupply can lead to failure in mitochondria dynamics including modifications in mitochondria fission and fusion, which are potentially linked to metabolic compromise and disease susceptibility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-fat diet induces long-term increase of peripheral IL-6 and fat deposits in dams and male offspring HFD has been associated with a variety of metabolic changes including increased body fat, obesity, diabetic-like phenotype (glucose and/or insulin intolerance) [72], and decreased fertility [73]. To characterize further our model, we assessed weight and food consumption, glucose levels, fat deposits, as well as gestation duration and litter size in the dams.…”
Section: Resultsmentioning
confidence: 99%